Development Serious Game as a Media for Mitigation Education Earthquake Disaster in Cerebral Palsy (CP) Students - Hastuti , Wiwik Dwi; Sudarjo, Sudarjo; Suyitno, Suyitno; Ramdani , Robitul Umam; Anantasya , Lia (Angstrom Centre of Education, 2025)
Cerebral palsy (CP) is a condition in children that has an impact on motoric and intelligence that is below average, causing the individual to be less able to adapt and make decisions in life, especially when there is a sudden earthquake disaster. In addition, not many learning media have been developed that are in accordance with the characteristics and needs of CP students. This study aims to develop a serious game as an educational medium for earthquake disasters for mentally retarded students. This study uses the ADDIE model from Lee & Owens, and the implementation is carried out on students with mental retardation in the learning process of earthquake disaster mitigation, which will be followed up in the revision of the final product. At the analysis stage, trials were carried out on the conditions of disaster mitigation learning practices at Tamima Mumtaz Special School as a research location with field visits and literature studies. The instrument used to assess product development uses a questionnaire aimed at media experts, material experts, practitioners and users, namely mentally retarded students. The results of the questionnaire will be analyzed using a mean analysis which in expert validation gets the final result 90.8% and in the media trial 88.1%. Descriptive data in the questionnaire was used as a basis for product development revisions. The conclusion is that serious games as an earthquake disaster mitigation medium for CP students are considered very feasible to be implemented as earthquake disaster mitigation media in the learning process of mentally retarded students.